INTEGRATING STAKEHOLDER PERSPECTIVES IN ECOLOGICAL-ECONOMIC PLANNING: A CASE STUDY OF KETAM ISLAND - Annisa Ilmi Faried; Dian Septiana Sari; Rahmad Sembiring; Saimara Sebayang; Nor Harlinda Binti Harun; Nisa Ulzannah (International Journal of Management, Economic and Accounting, 2025)
Effective ecological-economic planning requires systematic integration of diverse stakeholder perspectives to achieve sustainable development outcomes. This study examines how multi-stakeholder engagement frameworks can address the complex interplay between environmental conservation and economic advancement in ecologically sensitive coastal regions. Using Ketam Island, Malaysia as a case study, this research employs mixed-methods approach combining stakeholder analysis, participatory planning workshops, and environmental-economic impact assessments conducted from January to August 2025. The study engaged 425 stakeholders across six primary categories: local communities (n=180), government agencies (n=65), private sector entities (n=85), NGOs (n=45), academic institutions (n=30), and tourism operators (n=20). Results demonstrate that structured stakeholder integration mechanisms yield significant improvements in planning outcomes, with stakeholder satisfaction increasing from 42% to 78%, environmental indicators showing 23% improvement in marine biodiversity indices, and economic benefits demonstrating 47% increase in sustainable livelihood opportunities. The collaborative framework successfully bridged previously disconnected stakeholder groups, resulting in joint problem identification, shared solution development, and coordinated implementation strategies. This research contributes to understanding how participatory governance mechanisms can operationalize sustainability principles in practice.